FACTOR ANALYSIS OF HYPOGLICEMIA LEVEL IN EMERGENCY DEPARTMENT OF BLAMBANGAN AND GENTENG GENERAL HOSPITAL BANYUWANGI - Yusron Amin; Ahsan Ahsan; Tony Suharsono (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2017)
Hipoglycemia was a kind of acute complication of diabetes mellitus. Some factors was assumed associated with degree of hypoglycemia were infection, antidiabetic therapy, and leak of meal intake. This study was to analyse factors associated with degree of hypoglycemia in emergency department. Design was descriptive explorative with retrospective approach. Sum of respondents was 118 medical records. This study was conducted in medical record room in Blambangan hospital and Genteng Hospital from 5 June 2017 to 16 June 2017. Methods of data collection was purposive sampling. The results showed hypoglycemia was happened in majority of infection, using of unappropriate antidiabetic therapy and leak of meal intake. Infection factorsÂ (p=0,000; r=0,494), using of antidiabetic therapy (p=0,000; r=0,411), and leak of meal intake (p=0,000; r=0,619) had correlation with degree of hypoglycemia. Leak of meal intake factors (p=0,000; wald=27.897) had strongly correlation with degree of hypoglycemia. Health workers especially nurses was encouraged to conduct the intervention due to patientâ€™s self control, so that regulation of meal and antidiabetic therapy could work effectively.